Examining the Impact of Customer Relationship Management and Digital Marketing on Customer Choice: Evidence from Bank Muamalat Cirebon City - Shiska Nur Aini; Eef Saefulloh; Nur Haida (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2026)
This study aims to determine the effect of customer relationship management and digital marketing on customers' decisions in choosing Bank Muamalat KC Sumber. This study uses a quantitative approach with simple random sampling, a sample size of 100 respondents, and data analysis conducted using SmartPLS 4. The results of the study indicate that the Customer Relationship Management variable has a partially significant effect on customers' decisions, whereas the Digital Marketing variable does not. Furthermore, simultaneously, both independent variables have a significant effect on customers' decisions, with a contribution of 64.7%. Further research is expected to broaden the scope by adding variables used as decision- making factors, thereby enabling an increase in customers choosing Islamic banks.